Loss of Regulator of G protein signaling 5 promotes airway hyperresponsiveness in the absence of allergic inflammation - Balenga, Nariman A. (2014)
BACKGROUND: Although eosinophilic inflammation typifies allergic asthma, it is not a prerequisite for AHR, suggesting that underlying abnormalities in structural cells such as airway smooth muscle (ASM) contribute to the asthmatic diathesis. Dysregulation of procontractile, G protein-coupled receptor (GPCR) signaling in ASM could mediate enhanced contractility. OBJECTIVE: We explored the role of a regulator of procontractile GPCR signaling, RGS5, in unprovoked and allergen-induced AHR. METHODS: We evaluated GPCR-evoked Ca(2+) signaling, precision cut lung slice (PCLS) contraction, and lung inflammation in naïve and Aspergillus fumigatus-challenged WT and Rgs5(−/−) mice. We analyzed lung resistance and dynamic compliance in live, anesthetized mice by invasive plethysmography. RESULTS: Loss of RGS5 promoted constitutive AHR due to enhanced GPCR-induced Ca(2+) mobilization in ASM. PCLS from naïve Rgs5(−/−) mice contracted maximally at baseline, independent of allergen challenge. RGS5 deficiency had little effect on parameters of allergic inflammation including cell counts in bronchoalveolar lavage fluid (BALF), mucin production, ASM mass, and subepithelial collagen deposition. Unexpectedly, induced IL-13 and IL-33 were much lower in challenged lungs from Rgs5(−/−) mice relative to WT. CONCLUSION: Loss of RGS5 confers spontaneous AHR in mice in the absence of allergic inflammation. Because it is selectively expressed in ASM within the lung and does not promote inflammation, RGS5 may be a therapeutic target for asthma.